PERIODIZATION OF IGOR LUKASHUK'S RESEARCH ON THE LAW OF TREATIES - Yaremchuk, Vitalii (Lumen Publishing House, 2019)
The article is devoted to the periodization of Ukrainian scientist Igor Lukashuk's research on the law of treaties. Nowadays, there is a need to systematize and implement the periodization of his legal thoughts. It is conditionally possible to form the next periodization of Igor Lukashuk’s research on the law of treaties: the first stage is before the adoption of the Vienna Convention on the Law of Treaties (1969), and the second one is the implementation stage of the Vienna Convention. This can be explained by the fact that many Igor Lukashuk's legal ideas and proposals were researched long before the adoption of the Convention itself and subsequently found its own reflection in the text of the final edition document. In the second stage, after the adoption of the Vienna Convention on the Law of Treaties, Dr. Lukashuk researched the problems of using this fundamental document in practice. The scientist researched each of its parts, and particularly carefully analyzed the process itself of the adoption of the treaty.
Keywords: Law of treaties; Igor Ivanovich Lukashuk; legal thoughts; periodization; Vienna Convention on the Law of Treaties